Remuneration Practices in Funeral Rites in Parit Culum 1 Village: An Islamic Law Perspective - Rendi Pratama; Kurniawan; Alisyah Pitri (Zabags Qu Publish, 2025)
This study analyzes remuneration practices associated with funeral rites in Parit Culum 1 Village from the perspective of Islamic law. The research responds to the social reality that payments to individuals involved in funeral management have become an established local custom, yet remain underexplored within the fiqh frameworks of ijarah and ujrah. Employing a qualitative descriptive-analytical approach, the study combines primary field data gathered through observation, in-depth interviews, and documentation with a deductive analysis of relevant principles in muamalah fiqh. Findings indicate that funeral rites in the study area are organized through communal cooperation, and that remuneration, provided voluntarily in cash or in kind, is offered as an expression of appreciation for the services of funeral workers. These practices align with the key elements of ujrah under Islamic law, as they are grounded in voluntary consent, clear service provision, and the absence of coercion or commercialization of religious duty. The study contributes to fiqh muamalah scholarship by extending the application of ijarah to social-religious practices and by highlighting the legitimizing role of local custom (urf) in shaping legally acceptable, context-sensitive religious practices; it also offers an evidential basis for religious leaders and local policymakers to formulate normative guidance that reconciles sharīʿah principles with lived social realities.